Approach to fingering for performance of the piece Hungarian Fantasy op.65 no.1 for the modern classical guitar / Mohamed Shabyl Mohamed Ajmal - Mohamed Ajmal, Mohamed Shabyl (Faculty of Music, 2017)
The modern classical guitar is also more widely known as just the classical guitar. However, there is a slight need to include the word "modern", so that people do not confuse the instrument with earlier forms of the classical guitar such as the Romantic guitar. The Romantic guitar also had 6 strings, however the body and overall length of the instrument was slightly smaller, hence the stretches for the left hand on the instrument would be easier to play compared to on the modern classical guitar. According to an article by Morrish (n.d.), the person responsible for this change in size and design was Antonio de Torres, a Spanish luthier of the 19th century. The modern day classical guitars, and even acoustic guitars are derived from the Torres guitar model.